Etika Jawa Kurmat pada Karakter Tokoh Ranggalawe dalam Novel Ranggalawe: Sang Penakluk Mongol (Kajian Sosiologi Sastra) - Desy Proklawati (Journal on Education, 2023)
Ranggalawe figures are often used as figures in literary works. The character has an ethic that is loaded with Javanese ethics and can be exemplified from his stories. This study aims to describe the honorable character Ranggalawe in the novel Ranggalawe: the Mongol Conqueror by Makinudin. This research uses a qualitative approach with the type of literary sociology research. The research data is in the form of sentences in the novel with the data source in the form of a novel. "Ranggalawe: The Conqueror of the Mongols" by Makinudin. Based on data analysis, there are two types of respectful characters found in Ranggalawe's character: (1) respect for family and (2) respect for others. Respect for the family is shown by respect for the father and wife. Respect to others (respect shown by respecting guests and friends).